Poling pattern for efficient frequency doubling of Gaussian beams - Shiloh, Roy; Arie, Ady (Applied Physics B-Lasers and Optics, 2012)
The commonly used periodic patterning for quasi phase-matching plane-waves is theoretically adequate for completely depleting and transferring a fundamental wave to its second harmonic. However, when working with Gaussian beams the conversion efficiency of such a design lacks due to the inherent Gouy phase shift and the spatially varying beam profile, yielding roughly 88 % conversion efficiency. In this paper, we study the possibility of adding a linear chirp and Gouy-phase shift compensation to the periodic poling. We demonstrate that this poling pattern enables us to achieve near-optimal frequency doubling efficiency of up to 97 %. © 2012 Springer-Verlag.
Created from Fastlane, Scopus look-up